Paolaltica eocenica new genus and new species of flea beetle (Coleoptera: Chrysomelidae: Galerucinae: Alticini) from Baltic amber - Biondi, Maurizio (Zootaxa, 2014)
Paolaltica eocenica new genus and new species (Coleoptera: Chrysomelidae: Galerucinae: Alticini) is described and illustrated from Upper Eocene Baltic amber. The new taxon is compared with fossil and recent flea beetle genera.